A new species of Loricaria (Siluriformes: Loricariidae) from the Turiaçu River basin, Eastern Amazon region, Brazil - Saraiva, Ananda Carolina S.; Abreu, João Marcelo S.; Ottoni, Felipe Polivanov; Piorski, Nivaldo Magalhães (Zootaxa, 2021)
A new species of Loricaria is herein described from the Turiaçu River basin, Eastern Amazon region, Maranhão state, Brazil, within the Maranhão Hydrological Unit (MHU). Loricaria turi differs from its congeners mainly by the following combination of characters: abdominal plate development confined to the posterior median region, pectoral girdle mostly naked, with cluster of plates near pectoral fin bases; large eyes (minimum orbital diameter 16.2–20.7% of HL and maximum orbital diameter 19.8–24.0% of HL), 214.4 mm of maximum standard length, and large basicaudal plate (16.6–29.2% of HL). The description of this new species strengthens the hypothesis that the Maranhão Hydrological Unit (MHU) is a possible area of endemism for freshwater fishes and contributes to the knowledge of the freshwater fish diversity and composition of the region.